Rivalry, Uncertainty, and Militarized Compellent Threats. Issue 1 (13th February 2020) - Atkinson, Douglas B; Jackson, Joshua; Williford, George W
Abstract: Rivalry scholars have done much to explain how rivalries begin and how they end, but little explanation has been given to how rivalries are maintained over long periods of time. Existing theories treat maintenance as simply the absence of termination or the continuing presence of structural conditions that birthed the rivalry, but we argue that this is an unsatisfying conceptualization that does little to tell us what mechanisms keep rivalries going. We argue that rivalry maintenance is not a passive condition of nontermination. Rather, rivalries persist because uncertainty about an opponent's resolve periodically surfaces, and states eliminate this uncertainty by issuing threats designed to compel the enemy to make concessions on the underlying issue. States issue threats to signal their commitment to continue disputing the issue or to force their opponent to reveal their level of resolve. States must remain resolved if they do not wish to concede the issue(s) at stake. Rivalry maintenance is therefore a conscious decision by states to continue their rivalry in order to avoid granting concessions.